Reformulation of Children’s Restitution to Guarantee Their Constitutional Rights - Andre Arya Pratama (Constitutionale, 2023)
Children as victims of criminal acts of sexual violence essentially need to get the protection of the welfare and the right to return to grow and develop in accordance with the 1945 Constitution. Losses suffered by children need to be claimed through criminal compensation to the perpetrator or third person, namely the submission of the right to restitution. The mechanism for filing the right to restitution has certainly developed in the rule of law. However, until now it is still an obstacle for victims in fulfilling the filing requirements based on Government Regulation Number 43 of 2017. Of course this will make it difficult for victims to get justice as they should. This article will use normative research, where this research describes the analysis of the problems presented in the research using laws and regulations that refer to Law Number 31 of 2014 and Government Regulation Number  43 of 2017 in accordance with the scope of the discussion of applicable law and comes from literature journals and other sources of information that become references for the author to collect data to complete this research. The results show that the mechanism for implementing the right to restitution is difficult to implement, especially considering that victims tend to be unfamiliar with the law, besides that there are still perpetrators who generally come from the closest family and are not capable and have not regulated the nominal amount of payment that the perpetrator must fulfill. Therefore, it is necessary to reformulate the applicable regulations and related institutions need to play an active role in facilitating victims to fulfill the rights that should be obtained from a criminal offense as a form of effort to realize Human Rights (HAM) itself in the constitutional guarantees of citizens, especially children.